Pengaruh Variasi Massa Serat Pada Biokomposit Bioplastik Sari Pati Kentang Dan Serat Jerami Terhadap Kekuatan Bending Dan Water Absorption - Aswardi, Roccy Yusup; Kencanawati, Cok Istri Putri Kusuma; Atmika, I Ketut Adi (Teknik Desain Mekanika; Vol 13 No 1 (2024): Januari 2024 : Teknik Desain Mekanika, 2024)
Abstract This research used potato bioplastic matrix which composed of a mixture of potato starch, aquades, hardener, glycerol, and acetic acid which was then combined with rice straw fiber with fiber mass variations of 5%, 10%, 15%. Then printed with acrylic molding using the hand lay-up method. With suitable specimen sizes based on ASTM D790-03 for Bending Tests and ASTM D570-98 for Water Absorption Tests. The results of the bending test found that the highest bending stress and modulus of elasticity were found in a mass variation of 15% of the fiber, a bending stress value of 27.321 MPa, a modulus of elasticity of 2.031 GPa, and the lowest strain value of 0.784%. The highest bending strain is found in a 10% fiber mass variation of 1.428%, with a bending stress of 12.081 MPa. The smallest bending stress and modulus of elasticity are found in a mass variation of 5% of the fiber, with a stress value of 6.731 MPa, and a modulus of elasticity of 0.977 GPa. Water absorption obtained at a mass variation of 15% fiber has water absorption data with the highest average of 84.44%, compared to specimens of mass variation of 5% with the smallest average water absorption of 51%, while for mass variations of 10% an average water absorption of 64.03% is obtained. Keywords : Bioplastics, Biocomposites, Straw Fiber, Potato Starch, Water Absorption Test, Bending Test